Gaya Pengambilan Keputusan Kepala Sekolah dalam Meningkatkan Efektivitas Sekolah pada SMA Negeri di Kecamatan Kairatu Kabupaten Seram Bagian Barat - Welly Tomatala; Izaak Hendrik Wenno; Th. Laurens (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Decision making plays an important role in improving School Effectiveness. Principals can use various styles such as authoritative, consultative, delegative, facilitative and flexible styles, Rahabav (2021). Style variations in principal decision making are adapted to the situations and conditions of the problems faced by subordinates because the impact that arises is as a result of the decision style used by the principal. The purpose of this study 1) to describe the decision-making style of principals in high schools in Distric Kairatu West Seram Regency; 2) Describe School Effectiveness in SMA in Distric. Kairatu West Seram Regency; 3) Analyze the supporting and inhibiting factors for Principal Decision Making and School Effectiveness in SMA in Distric. Kairatu, West Seram Regency. The results of the study show that the Principal has used 5 decision-making styles and the dominant one used is the flexibility style (variation of styles). School effectiveness is in the Good category. Factors supporting the principal's decision- making style; a) The principal's awareness that the school is in an era of democratization b) The principal's commitment to respecting the role of teachers and education staff. Factors inhibiting decision-making style: a) The decisions taken are not based on data; b) Decision making does not pay attention to the main tasks and functions c) The principal listens more to input from senior teacher.